Opening up credit lines - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
'In the Caribbean, there are very few rural finance programmes for small farmers. Women face constraints both in applying for and obtaining credit. Some efforts have been made to extend loan facilities for women, micro-enterprises and for the...